Simultaneous Combined Myositis, Inflammatory Polyneuropathy, and Overlap Myasthenic Syndrome - Stéphane Mathis; Laurent Magy; Philippe Corcia; Karima Ghorab; Laurence Richard; Jonathan Ciron; Mathilde Duchesne; Jean-Michel Vallat (Case Reports in Neurological Medicine)
Immune-mediated neuromuscular disorders include pathologies of the peripheral nervous system, neuromuscular junction, and muscles. If overlap syndromes (or the association of almost two autoimmune disorders) are recognized, the simultaneous occurrence of several autoimmune neuromuscular disorders is rare. We describe two patients presenting the simultaneous occurrence of inflammatory neuropathy, myositis, and myasthenia gravis (with positive acetylcholine receptor antibodies). For each patient, we carried out a pathological analysis (nerve and muscle) and an electrophysiological study (and follow-up). To our knowledge, this is the first description of such a triple immune-mediated neuromuscular syndrome. We compared our observations with a few other cases of simultaneous diagnosis of two inflammatory neuromuscular disorders.